Delayed fracture union in a case of vitamin D dependent rickets associated with pulmonary tuberculosis - a case report - Mahajan, Neetin P.; G.S., Prasanna Kumar; Patil, Tushar C.; Jain, Kevin A. (International Journal of Research in Orthopaedics, 2021)
Rickets is a defect of bone mineralization caused by vitamin D deficiency, seen most significantly at growth plates that result in radiological bony abnormalities like metaphyseal flaring and cupping, physeal widening with focal and generalised osteomalacia. Here we present a rare case of 7 years old male, a case of vitamin D3 deficiency rickets in a known case of multi drug resistant pulmonary tuberculosis. The patient had suffered left proximal fibular fracture following trivial fall 1.5 month back and had delayed bony union leading to difficulty in walking and pain. The patient was treated with oral vitamin D supplementation. In vitamin D deficiency rickets, there is decreased bone mineralization leading to weak bones and delayed fracture healing in children. Low serum vitamin D levels also caused decreased immunity with increased susceptibility to respiratory infections like pulmonary tuberculosis. Appropriate treatment with injectable or oral vitamin D3 with adequate exposure of sunlight and proper nutrition is the best modality of treatment.